2010
DOI: 10.1021/la102446n
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Fabrication of Hydrogel Microparticles Containing Functionalized Viral Nanotemplates

Abstract: We demonstrate rapid microfluidic fabrication of hybrid microparticles composed of functionalized viral nanotemplates directly embedded in polymeric hydrogels. Specifically, genetically modified tobacco mosaic virus (TMV) templates were covalently labeled with fluorescent markers or metalized with palladium (Pd) nanoparticles (Pd-TMV), then suspended in a poly(ethylene glycol)-based solution. Upon formation in a flow-focusing device, droplets were photopolymerized with UV light to form microparticles. Fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 40 publications
2
71
0
Order By: Relevance
“…These unpolymerized films prevent the adhesion of polymerized structures to channel surfaces, allowing them to be harvested as particles. Numerous variations have been based upon this principle, including the fabrication of complex shape microparticles 24,30 , cell encapsulation 24 , and complex particle bar-coding 31,32 . Stop-flow lithography has allowed particles to be produced with arbitrary and precise two-dimensional shapes defined by the photo-mask.…”
Section: Introductionmentioning
confidence: 99%
“…These unpolymerized films prevent the adhesion of polymerized structures to channel surfaces, allowing them to be harvested as particles. Numerous variations have been based upon this principle, including the fabrication of complex shape microparticles 24,30 , cell encapsulation 24 , and complex particle bar-coding 31,32 . Stop-flow lithography has allowed particles to be produced with arbitrary and precise two-dimensional shapes defined by the photo-mask.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no lysine or cysteine residues exposed on the exterior surface of native TMV (39), X-ray structure of TMV revealed that the N-terminus, the C-terminus, and a loop between amino acid residues 55 and 60 of TMV were surface exposed (45). Through mutagenesis, surface accessible cysteine or lysine residues have been introduced to the N-terminus of TMV coat protein to produce stable virions, which could be subsequently functionalized (39, 44, 4648). In our study, a cysteine mutant of TMV (TMV1cys) (46, 48), which contains a cysteine residue inserted between Ser 2 and Tyr 3 of the TMV coat protein, was used for the conjugation with the Tn antigen.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the infusibility of P(VDF-TrFE) in water, the DMF was chosen as the solution, and the UVcured was selected as solidification. 32 Both of the dispersed phases were added to 34% (v/v) poly(ethylene glycol) diacrylate (PEG-DA, Sigma Aldrich, St. Louis, MO, MW $ 575, q ¼ 1.12 g/ml, l ¼ 70 cP) as a photocurable monomer and 6% (v/v) 2-hydroxy-2-methylpropiophenone (Darocur 1173, Sigma Aldrich, St. Louis, MO, MW ¼ 164.2, q ¼ 1.077 g/ml, l ¼ 25 cP) as a photoinitiator for UV-initiated polymerization. 33 The two dispersed phases were then injected into the microchannels independently using syringe pumps (TS2-60, Longer Precision Pump Corporation, Ltd.) to form parallel laminar flow in the upstream channel ( Fig.…”
Section: B Reagents and Materials Mixing Processingmentioning
confidence: 99%